Dataset associated with 'Quantification of Ebola virus replication kinetics in vitro' - Liao, Laura; Carruthers, Jonathan; Smither, Sophie; CL4 Virology Team; Weller, Simon; Williamson, Diane; Laws, Thomas; García Dorival, Graciela Isabel; Hiscox, Julian; Holder, Benjamin; Beauchemin, Catherine; Perelson, Alan; et al. (University of Leeds, 2020)
This dataset is associated with ‘Quantification of Ebola virus replication kinetics in vitro’. In the paper, a mathematical model is developed to describe the replication of Ebola virus in Vero cells. The model is parametrised using measurements of total and infectious extracellular virus at three different multiplicities of infection. The results provide insights into the distribution of time an infected cell spends in the eclipse phase (the period between infection and the start of virus production), as well as the rate at which infectious virions lose infectivity. Here, we provide all the experimental results necessary to parametrise the mathematical model.
Keywords: FOS: Mathematics; Virology